Re-admission Rate of Patients with Ureteral Stone: A Descriptive Study - Forouzanfar, Mohammad Mehdi; Ghiasy, Saleh; Majidi, Alireza; Hashemi, Behrooz; Sanei Taheri, Morteza; Ghodsi, Mahsa (Archives of Men's Health, 2020)
Introduction: Patients with acute renal colic need to choose between undergoing medical treatments and receiving interventions. The Aim of this study is to evaluate the outcomes of patients who are discharged from emergency departments with ureteral stones lesser than 6 millimeters. In doing so, the effect of diagnostic treatment approaches on clinical outcomes and referral rate is to be assessed. Patients and Methods: This study was performed on patients with ureteral stones referred to emergency department of Shohadaye Tajrish Hospital between May2015 to June 2018. A checklist was filled out for each patient and it included their complete medical history, physical examination results and paraclinical data. Patients were then studied for 4 weeks to determine referral times to hospital and clinical outcomes. Results: 105 patients include 81 men (77.14%) with average age of 37.1±12.4 years were studied. The mean stone diameter was 4.2±2.1 mm. Most of ureteral stones were seen in the right-hand side (60 percent). 71 patients (67.6%) did not have any history of nephrolithiasis and 73 (69.5%) did not have positive family history for nephrolithiasis. Ureteral stones were still observed in 42 patients (40%) after two weeks of studies and only one patient (1.1%) had stone in Ultrasound Imaging after 4 weeks of observations. Conclusion: Most Patients (95%) with stones smaller than 6 mm responded to Medical Expulsive Therapy (MET) after 4 weeks and passed spontaneously ureteral calculi.